A brief and practical guide to EU law - Medhurst, David (Oxford ; Malden, MA : Blackwell Science, 2001)
This book is designed to be a quick guide to European Union law and explains how it may be used for practical effect. It is written in a clear style for practitioners who are in a hurry to master the subject, and contains precedents of the kinds of documents they may have to prepare. It explains the basic law, the basic concepts, the procedure and the jargon in a way that lawyers new to the subject will find easy to understand. It will give them the answers they need fast. Throughout, there is extensive reference to case law. The new edition has been revised to take into account the 1997.
The treaties -- The institutions -- Legislation -- Interpretation and research -- The court -- Procedure -- Effective use of EC law -- Pleadings -- Free movements of goods -- Free movement of persons -- Freedom of establishment and provision of services -- Competition -- Company law -- Social policy -- The common agricultural policy.
Includes bibliographical references (pages 210-211) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Law -- European Union countries; Law; European Union countries; 2; Recht; 2